Methylated [(arene)(1,3-cyclohexadiene)Ru(0)] complexes as low-melting MOCVD precursor complexes with a controlled follow-up chemistry of the ligands - Jipa, Ilona; Danova, Katia; Popovska, Nadejda; Siddiqi, M. Aslam; Siddiqui, Rehan A.; Atakan, B.; Cremer, Till; Maier, Florian; Marbach, Hubertus; Steinrück, Hans-Peter; Heinemann, Frank Wilhelm; Zenneck, Ulrich (Journal of Materials Chemistry, 2011)
[(Benzene)(2-methyl-1,3-cyclohexadiene)Ru(0)] (1), [(1,3-cyclohexadiene) (toluene)Ru(0)] (2), and [(methyl-cyclohexadiene)(toluene)Ru(0)] (3, mixture of isomers) have been prepared and tested as new metal organic ruthenium precursor complexes for chemical vapor deposition (MOCVD) with favorable properties. 1 is a low-melting precursor complex (mp = 29 °C) and the isomeric mixture 3 forms a liquid at room temperature. X-ray diffraction studies of single crystals of complexes 1 and 2 are characteristic for true Ru(0) π-complexes without molecular structure peculiarities or significant intermolecular interactions in the solid state, which could hinder undecomposed evaporation. Differential thermal analysis (DTA), differential scanning calorimetry (DSC) and vapor pressure data qualify the compounds as almost ideal MOCVD precursors. Thin ruthenium films have been deposited successfully on silicon wafers and substrate temperatures between 200 and 450 °C in inert gas atmospheres. Film growth and properties were evaluated by scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and four-point probe conductivity measurements. All films consist of polycrystalline metallic ruthenium with a low surface roughness. © The Royal Society of Chemistry 2011.